(untitled) (Zaporizhzhia Historical Review, 2021)
The Modern Ukrainian organs of control have serious problems, such as the soviet organs of control in 1920-1930-th. This scientific research is dedicated to the study of the processes of the forming and activity of Central control commission of Communist party and Workers-Peasants inspections in 1920-1930-th.